External debt-economic growth nexus in selected CEE countries - Çiftçio?lu, Serhan; Sokhanvar, Amin (Institute for Economic Forecasting rjef@ipe.ro, 2018)
This paper presents new evidence regarding the potential adverse effects of external debt on long-run economic growth in a sample of twelve emerging economies of Central and Eastern Europe (CEE). The empirical findings of the paper suggest that policy makers in many of CEE countries should be encouraged to evaluate the long-run costs and benefits of existing fully liberalized capital account regimes which allow both private and public sectors to finance their expenditures by external borrowing. These basic insights of the paper are obtained from the application of panel regression and Granger causality analysis for a sample of twelve CEE countries using annual data for the period of 1995-2014. The Granger causality tests have shown that there is a statistically significant causal effect of external debt on economic growth in eight countries. © 2018, Institute for Economic Forecasting. All rights reserved.
Keywords: External debt; GDP growth; Inflation; Investment; Trade openness